Inovasi Produk Sosis Solo dan Strategi Marketing melalui Media : Solo Sausage Product Innovation and Marketing Strategy through Media - Yunio Dwi Arizki; Basuki (AKSILAR: Akselerasi Luaran Pengabdian Masyarakat, 2023)
Since the government implemented the PSBB and work from home, many business owners have been affected by this policy, one of which is in the economic sector. The owner of a business such as Solo Sausage Food is one example of the many business sectors. Because the basis of selling solo sausage food is that it is marketed by traveling from house to house or selling to markets, many markets are still closed due to market traders being infected with the COVID-19 virus, and the government has announced that the market is one of the clusters. new spread of COVID-19 in Indonesia currently. This is one of the problems of traders, one of whom is the owner of a solo sausage food business, who has lost one of his market victims or whose place where he sells his product is not selling optimally. By looking at these problems, the author is interested in assisting the solo sausage food business, which is affected by the COVID-19 virus pandemic, by carrying out product innovation and marketing strategies through online media, starting with the Instagram, Facebook, and WhatsApp platforms. Where one of these programs is able to increase income and the product can be maximally absorbed by the community.